Pengembangan Media Pembelajaran Geografi Berbasis Aplikasi Prezi Di SMA Negeri 1 Suwawa Provinsi Gorontalo - Puluhulawa, Nur Fakriya; Maryati, Sri; Yusuf, Daud (Universitas Negeri Gorontalo, 2024)
Development of Prezi Application-Based Learning Media in Geography Subjects, Material on Diversity of Indonesian Flora and Fauna.